Sheet for workpiece processing and method for manufacturing processed workpiece

By using an active energy ray curable adhesive layer containing alkylene glycol modified rosin ester and a hindered amine-based stabilizer in the workpiece processing sheet, the active surface of the workpiece is solved by using the active energy ray in the workpiece processing sheet. The problem of excessive degradation of the adhesiveness achieves stable bonding of the workpiece and subsequent easy separation.

CN119505737APending Publication Date: 2025-02-25LINTEC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411160969.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-01
Filing Date
2024-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing workpiece processing sheets excessively reduce the active surface of the workpiece before the active energy rays are irradiated, resulting in unexpected falloff or offset of the workpiece and cannot be picked up well during the pickup process.

Method used

The active energy ray curable adhesive layer containing alkylene glycol modified rosin ester and hindered amine-based stabilizer is used to ensure that the active surface of the workpiece is displayed with good adhesion before the active energy ray is irradiated, and after the irradiation is irradiated, it is It can cure well and reduce adhesion.

Benefits of technology

The stable adhesion to the workpiece before the active energy ray is irradiated, the workpiece is avoided accidentally falling off or offset, and the workpiece can be easily separated after the irradiation, improving the pickup effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

Provided are: a workpiece processing sheet which exhibits good adhesion to an active surface of a workpiece before irradiation with an active energy ray, and which enables good separation of the workpiece after irradiation with the active energy ray; and a method for manufacturing a processed workpiece using the workpiece processing sheet. The sheet for workpiece processing is provided with a base material and an adhesive layer laminated on one surface side of the base material, and the adhesive layer is composed of an active energy ray-curable adhesive containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer. The workpiece processing sheet is used for being attached to the polished surface of the workpiece within 120 minutes from the surface of the polished workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a workpiece processing sheet that can be suitably used for processing a workpiece such as a semiconductor wafer and a method for manufacturing a workpiece processed using the workpiece processing sheet. The present invention particularly relates to a workpiece processing sheet that can be suitably used for processing a workpiece having a surface in an active state (hereinafter sometimes referred to as an "active surface") and a method for manufacturing a workpiece processed using the workpiece processing sheet. Background Art

[0002] Semiconductor wafers such as silicon and gallium arsenide and various packages are manufactured in a large diameter state, cut (diced) into small component pieces (semiconductor chips), peeled (picked up), and transferred to the mounting process as a subsequent process. At this time, the workpiece such as the semiconductor wafer is attached to the workpiece processing sheet with a substrate and an adhesive layer, and back grinding, dicing, cleaning, drying, expanding (expanding), picking up, mounting and other processes are performed.

[0003] In the back grinding process, the workpiece is usually fixed on the workpiece processing sheet, and the exposed surface of the workpiece is ground using a grinding device. In the cutting process, the ground workpiece is cut on the workpiece processing sheet and singulated into multiple chips. And in the picking process, the multiple chips obtained are picked up one by one from the workpiece processing sheet.

[0004] The workpiece that has been ground on one side in the back grinding process is sometimes re-attached to a new workpiece processing sheet before the grinding process. At this time, the surface on the adhesive layer side of the new workpiece processing sheet (hereinafter sometimes referred to as the "adhesive surface") is attached to the ground surface, and the previous workpiece processing sheet is peeled off.

[0005] In recent years, the above-mentioned grinding, re-lamination and cutting processes are sometimes performed continuously in an inline manner. In this case, the workpiece processing sheet is attached to the grinding surface of the workpiece immediately after grinding.

[0006] Here, usually, the grinding surface of the workpiece just after grinding is in an activated state due to grinding. Therefore, when the workpiece processing sheet is attached immediately after grinding the workpiece, the workpiece processing sheet will be attached to the active surface of the workpiece. At this time, since the active surface is active, the closeness between the workpiece and the workpiece processing sheet is prone to excessive increase. In particular, the longer the time in which the workpiece and the workpiece processing sheet are stacked, the more the closeness tends to increase. In addition, when the workpiece and the workpiece processing sheet are overly close in this way, in the subsequent picking process, since the obtained chip is in a state of strongly close to the workpiece processing sheet, it cannot be picked up well.

[0007] Usually, from the perspective of good picking up, a workpiece processing sheet having an adhesive layer composed of an adhesive having active energy ray curability is also used. In this case, the adhesive layer is irradiated with active energy rays just before picking up to cure the adhesive layer, thereby reducing the adhesion to the chip and making it easier to separate the chip. However, even when such a workpiece processing sheet is used, it is still difficult to avoid the problem of not being able to pick up well as described above.

[0008] In order to solve the above-mentioned problem of increased adhesion to the active surface of a workpiece, Patent Document 1 discloses a workpiece processing sheet including an active energy ray-curable adhesive layer containing an alkylene glycol-modified rosin ester as a tackifier.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent No. 7254669 Summary of the invention

[0012] 1. Technical issues to be resolved

[0013] According to the workpiece processing sheet disclosed in Patent Document 1, even when attached to the active surface of the workpiece, the adhesion to the workpiece after irradiation with active energy rays can be well reduced, and good picking can be performed. However, the inventors of the present application have confirmed that the workpiece processing sheet has a tendency to reduce the adhesion to the workpiece even before irradiation with active energy rays, and as a result, the workpiece may accidentally fall off or shift.

[0014] The present invention has been completed in view of the above-mentioned actual situation, and its purpose is to provide a workpiece processing sheet and a method for manufacturing a processed workpiece using the workpiece processing sheet, wherein the workpiece processing sheet shows good adhesion to the active surface of the workpiece before irradiation with active energy rays, and can perform good workpiece separation after irradiation with active energy rays.

[0015] (II) Technical solution

[0016] In order to achieve the above-mentioned purpose, first, the present invention provides a workpiece processing sheet, which comprises a substrate and an adhesive layer laminated on one side of the substrate, the workpiece processing sheet is characterized in that the adhesive layer is composed of an active energy ray-curable adhesive containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer, and the workpiece processing sheet is used to adhere to the polished surface of the workpiece within 120 minutes from the polishing of the surface of the workpiece (Invention 1).

[0017] In the workpiece processing sheet of the above invention (Invention 1), the adhesive layer is composed of an active energy ray-curable adhesive containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer. Therefore, even when the sheet is attached to the active surface of the workpiece, it exhibits sufficient adhesion to the workpiece before irradiation with active energy rays, and after irradiation with active energy rays, the adhesive layer is well cured, thereby the adhesion to the workpiece is well reduced. Therefore, the workpiece processing sheet can prevent the workpiece from accidentally falling off or shifting, and can easily separate the workpiece even after being attached to the active surface of the workpiece and stored for a long time, for example.

[0018] In the above invention (Invention 1), the hindered amine stabilizer is preferably an N-alkyl hindered amine stabilizer (Invention 2).

[0019] In the above inventions (Inventions 1 and 2), it is preferred that the molecular weight of the hindered amine stabilizer is 500 or more (Invention 3).

[0020] In the above inventions (Inventions 1 to 3), it is preferred that the weight average molecular weight of the alkylene glycol-modified rosin ester is 1,000 or more (Invention 4).

[0021] In the above inventions (Inventions 1 to 4), the active energy ray-curable adhesive is preferably formed from an adhesive composition containing an acrylic polymer having an active energy ray-curable group introduced into a side chain, the alkylene glycol-modified rosin ester and the hindered amine stabilizer (Invention 5).

[0022] In the above invention (Invention 5), it is preferred that the adhesive composition contains an antistatic agent (Invention 6).

[0023] Second, the present invention provides a method for manufacturing a processed workpiece, characterized in that the manufacturing method comprises: a grinding step for grinding the surface of the workpiece; an attaching step for attaching the workpiece processing sheet (Inventions 1 to 6) to the grinded surface of the workpiece; a cutting step for cutting the workpiece on the workpiece processing sheet to obtain a plurality of chips formed by singulating the workpiece; an active energy ray irradiation step for irradiating the adhesive layer in the workpiece processing sheet with active energy rays; and a picking up step for picking up the chips one by one from the workpiece processing sheet (Invention 7).

[0024] In the above invention (Invention 7), it is preferred that the workpiece processing sheet be attached to the workpiece in the attaching step be attached within 120 minutes from the polishing of the surface of the workpiece in the polishing step (Invention 8).

[0025] (III) Beneficial effects

[0026] The workpiece processing sheet of the present invention exhibits good adhesion to the active surface of the workpiece before irradiation with active energy rays and can separate the workpiece well after irradiation with active energy rays. In addition, according to the manufacturing method of the present invention, a processed workpiece can be manufactured well. DETAILED DESCRIPTION

[0027] Hereinafter, embodiments of the present invention will be described.

[0028] The workpiece processing sheet of this embodiment comprises a substrate and an adhesive layer laminated on one side of the substrate. In addition, the adhesive layer is composed of an active energy ray-curable adhesive containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer. Furthermore, the workpiece processing sheet of the embodiment is used to be attached to the polished surface of a workpiece within 120 minutes from the polishing of the surface of the workpiece.

[0029] In the workpiece processing sheet of the present embodiment, the adhesive layer is composed of an active energy ray-curable adhesive, and the adhesive layer can be cured by irradiating active energy rays, thereby reducing the adhesive force to the workpiece. Therefore, when it is necessary to separate the workpiece processing sheet of the present embodiment from the workpiece, it is possible to prevent the workpiece from being damaged or part of the adhesive constituting the adhesive layer from being attached to the workpiece (residual adhesive), and the separation can be easily performed.

[0030] Furthermore, in the workpiece processing sheet of the present embodiment, by making the above-mentioned active energy ray-curable adhesive contain alkylene glycol-modified rosin ester and hindered amine stabilizer, it is possible to exhibit sufficient adhesion to the workpiece before irradiation with active energy rays. Furthermore, even when the workpiece processing sheet is attached to the active surface of the workpiece and further stored for a long time in the attached state, it is possible to suppress excessive increase in adhesion to the workpiece. Thus, the workpiece processing sheet can be easily separated from the workpiece by irradiating the active energy ray as described above.

[0031] The reason why the excessive increase in adhesion to the workpiece after irradiation with active energy rays in the workpiece processing sheet of the present embodiment is suppressed is estimated as follows, but the reason is not limited to this.

[0032] First, as the mechanism of activation of the surface of the workpiece, it is believed that by grinding the surface of the workpiece, the inactive part present on the surface is removed, exposing the active part inside. For example, when the workpiece is a silicon wafer, it is believed that under normal conditions, the surface of the silicon wafer is oxidized to form an inactive SiO2 film. If the surface of such a silicon wafer is ground, the SiO2 film will be removed to expose silicon atoms in an unoxidized state. In addition, the exposed silicon atoms sometimes react with the cleaning water or moisture in the atmosphere used in the back grinding process, etc., and partially form a structure of Si-H or Si-OH. In this way, the surface exposed by removing the SiO2 film is in a state that is easy to interact with the adhesive surface of the usual workpiece processing sheet and is easy to produce a chemical bond with the adhesive constituting the adhesive layer.

[0033] In addition, it is also believed that grinding the surface of the workpiece causes free radicals to be generated on the surface, thereby presenting a state in which the surface is activated. For example, on the ground surface, free radicals (R·) are first generated due to hydrogen being taken from the RH group. Then, a portion of the free radicals (R·) reacts with oxygen molecules in the air to generate peroxy radicals (ROO·). Moreover, a portion of it takes hydrogen from the RH group to generate hydroperoxide (hydroperoxide) (ROOH) and free radicals (R·). Further, a portion of the generated hydroperoxide (ROOH) decomposes to generate oxygen radicals (RO·) and hydroxyl radicals (·OH). In this way, the surface that generates a large number of free radicals is in a state in which it is easy to interact with the adhesive surface of the usual workpiece processing sheet and is easy to produce chemical bonds with the adhesive constituting the adhesive layer.

[0034] Next, the mechanism by which the workpiece processing sheet of the present embodiment can suppress excessive increase in adhesion even to the active surface of the workpiece produced as described above is considered as follows. Usually, the above-mentioned adhesive composition is used to form a coating film, and the coating film is cured to form the adhesive layer in the present embodiment. Here, the molecular weight of the alkylene glycol-modified rosin ester contained in the adhesive composition is relatively large, and the compatibility with other components contained in the adhesive composition is relatively low. Further, the fluidity of the alkylene glycol-modified rosin ester at room temperature is relatively high, and it is easy to move in the adhesive composition. In this way, the low compatibility between the alkylene glycol-modified rosin ester and other components and the easy movement in the adhesive composition are coordinated, so that in the coating film formed using the adhesive composition, the alkylene glycol-modified rosin ester is easy to move to the coating surface. By curing such a coating film, an adhesive layer is formed in which the alkylene glycol-modified rosin ester is unevenly distributed near the surface, and as a result, in the workpiece processing sheet of the present embodiment, the alkylene glycol-modified rosin ester is unevenly distributed near its adhesive surface. In addition, it is believed that the alkylene glycol-modified rosin ester present near the adhesive surface acts in a manner that suppresses the interaction or chemical bond with the active surface of the workpiece as described above, and it is believed that the excessive increase in the adhesion between the active surface of the workpiece and the workpiece processing sheet of the present embodiment is suppressed.

[0035] Furthermore, in the workpiece processing sheet of the present embodiment, it is believed that the hindered amine stabilizer or the stable free radicals generated in the system from the hindered amine stabilizer captures the free radicals generated as described above and inactivates them, thereby suppressing the interaction with the active energy ray-curable adhesive or the generation of chemical bonds. As a result, the workpiece processing sheet of the present embodiment can effectively suppress the increase in adhesion with the active surface.

[0036] In particular, it is believed that the hindered amine stabilizer can capture at least three of the above-mentioned multiple free radicals, namely, R·, RO·, and ROO·. In contrast, other stabilizers (hindered phenol stabilizers, phosphite stabilizers, etc.) can capture fewer types of free radicals, or cannot capture free radicals at all. Therefore, the workpiece processing sheet of this embodiment can effectively suppress the increase in adhesion to the active surface by using a hindered amine stabilizer.

[0037] In addition, after the hindered amine stabilizer captures the free radical (bonds with the free radical), it reacts to disconnect the free radical part again and regenerates as a hindered amine stabilizer. Therefore, the hindered amine stabilizer can continuously exert its effect as a stabilizer. In addition, in the hindered phenol compounds used in the past, such a regeneration effect does not occur. From this perspective, the workpiece processing sheet of this embodiment can effectively suppress the increase in adhesion with the active surface.

[0038] The effect of the alkylene glycol-modified rosin ester as described above is synergistic with the effect of the hindered amine stabilizer, so the workpiece processing sheet of this embodiment suppresses excessive increase in adhesion to the workpiece, and can easily separate the workpiece by irradiation with active energy rays. In addition, the workpiece processing sheet of this embodiment can suppress the problem of excessive decrease in adhesion to the workpiece before irradiation with active energy rays that occurs when the alkylene glycol-modified rosin ester is used alone by using the alkylene glycol-modified rosin ester and the hindered amine stabilizer. In summary, according to the workpiece processing sheet of this embodiment, good workpiece processing can be performed.

[0039] In addition, in the specification of the present application, the surface of the workpiece being in an activated state refers to a state within 120 minutes from the time the surface of the workpiece is polished, preferably a state within 30 minutes from the time the surface of the workpiece is polished, and more preferably a state within 5 minutes from the time the surface of the workpiece is polished.

[0040] In addition, the shelf life of the stack of the workpiece and the workpiece processing sheet after the workpiece processing sheet of this embodiment is attached to the active surface of the workpiece can be set according to the purpose of use. Usually, the shelf life is mostly 0 to 500 days, especially mostly 1 to 90 days, and further mostly 7 to 30 days.

[0041] 1. Substrate

[0042] The substrate of the present embodiment is not particularly limited as long as it plays the required function when using the workpiece processing sheet. It is particularly preferred that the substrate of the present embodiment is composed of a resin. As examples of the resin, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate can be listed; polyolefin resins such as polyethylene, polypropylene, polybutene, polybutadiene, polymethylpentene, ethylene-norbornene copolymer, and norbornene resin; ethylene-vinyl acetate copolymer; ethylene-(meth) acrylic acid copolymer, ethylene-(meth) methyl acrylate copolymer, and other ethylene-(meth) acrylic acid ester copolymers and other ethylene copolymer resins; polyvinyl chloride, vinyl chloride copolymers and other polyvinyl chloride resins; (meth) acrylic acid ester copolymers; polyurethane; polyimide; polystyrene; polycarbonate; fluororesin, etc. In addition, the resin constituting the substrate can be a modified resin such as a resin obtained by cross-linking the above-mentioned resin or an ionomer of the above-mentioned resin. In addition, "(meth) acrylic acid" in this specification refers to both acrylic acid and methacrylic acid. Other similar terms are also the same. In addition, the "polymer" in this specification also includes the concept of "copolymer".

[0043] The substrate of this embodiment may be a single-layer film composed of the above-mentioned resin, or may be a laminated film in which a plurality of such films are laminated. In the laminated film, the materials constituting each layer may be of the same type or of different types.

[0044] The substrate may contain various additives such as flame retardants, plasticizers, antistatic agents, lubricants, antioxidants, colorants, infrared absorbers, ultraviolet absorbers, ion traps, etc. The content of these additives is not particularly limited, but is preferably within a range in which the substrate can exert the desired function.

[0045] Furthermore, the substrate preferably has transparency to active energy rays. By using such a substrate, even when the adhesive layer is irradiated with active energy rays through the substrate, the adhesive layer can be easily cured well.

[0046] Furthermore, in order to improve the adhesion with the adhesive layer, the surface of the substrate on which the adhesive layer is to be laminated may be subjected to a surface treatment such as a primer treatment, a corona treatment, or a plasma treatment.

[0047] The thickness of the substrate can be appropriately set according to the method of using the workpiece processing sheet, and is, for example, preferably 200 μm or less, particularly preferably 150 μm or less. In addition, the thickness of the substrate is preferably 10 μm or more, particularly preferably 25 μm or more.

[0048] 2. Adhesive layer

[0049] As described above, the adhesive layer of the present embodiment is composed of an active energy ray-curable adhesive containing an alkylene glycol-modified rosin ester and a hindered amine-based stabilizer.

[0050] Examples of the adhesive include, but are not particularly limited to, acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, polyester adhesives, polyvinyl ether adhesives, etc. Among them, acrylic adhesives are preferably used because they are easy to form active energy ray-curable adhesives and are easy to exert the required adhesive force.

[0051] In addition, as the above-mentioned active energy ray curing adhesive, it can be a polymer with active energy ray curing as the main component, or a mixture of a non-active energy ray curing polymer (a polymer without active energy ray curing) and a monomer and / or oligomer having at least one active energy ray curing group as the main component. Further, the active energy ray curing adhesive can also be a mixture of a polymer with active energy ray curing and a monomer and / or oligomer having at least one active energy ray curing group. Among them, as the active energy ray curing adhesive of the present embodiment, from the perspective of being able to suppress the adverse effects caused by excessive increase in adhesion even after heat treatment and being easy to separate the workpiece well by using a trigger (trigger) to reduce the adhesion, it is preferred to use a polymer with active energy ray curing (particularly an acrylic polymer with active energy ray curing) as the main component.

[0052] The above-mentioned active energy ray-curable acrylic polymer is preferably an acrylic polymer having an active energy ray-curable functional group (active energy ray-curable group) introduced into the side chain (hereinafter, sometimes referred to as "active energy ray-curable polymer (A)"). In this case, the active energy ray-curable adhesive of the present embodiment is preferably formed by an adhesive composition containing an acrylic polymer having an active energy ray-curable group introduced into the side chain (active energy ray-curable polymer (A)), an alkylene glycol-modified rosin ester, and a hindered amine stabilizer.

[0053] (1) Active energy ray-curable polymer (A)

[0054] The active energy ray-curable polymer (A) is preferably obtained by reacting a (meth)acrylate polymer (a1) having a monomer unit containing a functional group with an unsaturated group-containing compound (a2) having a functional group bonded to the functional group of (a1).

[0055] The functional group-containing monomer is preferably a monomer having a polymerizable double bond and a functional group such as a hydroxyl group, a carboxyl group, an amino group, an amide group, a benzyl group, or a glycidyl group in the molecule. Among them, a monomer containing a hydroxyl group as a functional group (hydroxyl group-containing monomer) is preferably used.

[0056] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among them, at least one of 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate is preferably used. In addition, these hydroxyl-containing monomers may be used alone or in combination of two or more.

[0057] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. These carboxyl group-containing monomers may be used alone or in combination of two or more.

[0058] Examples of the amino group-containing monomer or amide group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These amino group-containing monomers or amide group-containing monomers may be used alone or in combination of two or more.

[0059] The (meth)acrylate polymer (a1) preferably contains 5% by mass or more of structural units derived from the above-mentioned functional group-containing monomers, and particularly preferably contains 10% by mass or more of structural units derived from the above-mentioned functional group-containing monomers. In addition, the (meth)acrylate polymer (a1) preferably contains 40% by mass or less of structural units derived from the above-mentioned functional group-containing monomers, and particularly preferably contains 35% by mass or less of structural units derived from the above-mentioned functional group-containing monomers. By allowing the (meth)acrylate polymer (a1) to contain the functional group-containing monomers within the above range, it is easy to form the desired active energy ray-curable polymer (A).

[0060] From the viewpoint of easily forming an adhesive having the desired properties, the (meth)acrylate polymer (a1) preferably contains an alkyl (meth)acrylate as a monomer unit constituting the (meth)acrylate polymer (a1). As the alkyl (meth)acrylate, an alkyl (meth)acrylate having an alkyl group with 1 to 18 carbon atoms is preferred, and an alkyl (meth)acrylate having 1 to 8 carbon atoms is particularly preferred.

[0061] Specific examples of the above-mentioned alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearic (meth)acrylate, etc. These alkyl (meth)acrylates may be used alone or in combination of two or more. Among the above-mentioned alkyl (meth)acrylates, at least one of n-butyl (meth)acrylate and 2-ethylhexyl acrylate is preferably used.

[0062] The (meth)acrylate polymer (a1) preferably contains 20% by mass or more of structural units derived from the above-mentioned alkyl (meth)acrylate, and particularly preferably contains 30% by mass or more of structural units derived from the above-mentioned alkyl (meth)acrylate. In addition, the (meth)acrylate polymer (a1) preferably contains 95% by mass or less of structural units derived from the above-mentioned alkyl (meth)acrylate, and particularly preferably contains 85% by mass or less of structural units derived from the above-mentioned alkyl (meth)acrylate. By making the (meth)acrylate polymer (a1) contain the alkyl (meth)acrylate in the above-mentioned range, the workpiece processing sheet can easily exert the required adhesive force.

[0063] The (meth)acrylate polymer (a1) may contain other monomers as monomer units constituting the (meth)acrylate polymer (a1), in addition to the above-mentioned functional group-containing monomer and the (meth)acrylate alkyl ester.

[0064] Examples of the other monomers include: nitrogen atom-containing monomers; (meth)acrylates containing alkoxyalkyl groups such as methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, and ethoxyethyl (meth)acrylate; (meth)acrylates having an aliphatic ring such as cyclohexyl (meth)acrylate; (meth)acrylates having an aromatic ring such as phenyl (meth)acrylate; non-crosslinking acrylamides such as (meth)acrylamide and N,N-dimethyl (meth)acrylamide; non-crosslinking (meth)acrylates having a tertiary amino group such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; styrene, and the like.

[0065] Examples of the nitrogen atom-containing monomers include monomers having an amino group, monomers having an amide group, monomers having a nitrogen-containing heterocyclic ring, etc. Further, examples of monomers having a nitrogen-containing heterocyclic ring include N-(meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylaziridine, aziridinylethyl(meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide.

[0066] The (meth)acrylate polymer (a1) also preferably uses a monomer having a glass transition temperature (Tg) of more than 10° C. as a homopolymer as a monomer unit constituting the (meth)acrylate polymer (a1). Examples of such monomers include vinyl acetate, N-(meth)acryloylmorpholine, and methyl methacrylate. When the above monomers are used, the (meth)acrylate polymer (a1) preferably contains 10% by mass or more and 60% by mass or less of a structural unit derived from the above monomer.

[0067] The polymerization form of the (meth)acrylate polymer (a1) may be a random copolymer or a block copolymer. The polymerization method is not particularly limited, and the polymerization can be carried out by a common polymerization method, for example, a solution polymerization method.

[0068] The active energy ray-curable polymer (A) can be obtained by reacting the (meth)acrylate polymer (a1) having the functional group-containing monomer unit and the unsaturated group-containing compound (a2) having a functional group bonded to the functional group of (a1).

[0069] The functional group of the unsaturated group-containing compound (a2) can be appropriately selected according to the type of functional group of the functional group-containing monomer unit of the (meth)acrylate polymer (a1). For example, when the functional group of the (meth)acrylate polymer (a1) is a hydroxyl group, an amino group or a carboxyl group, the functional group of the unsaturated group-containing compound (a2) is preferably an isocyanate group, an epoxy group or an aziridine group, and when the functional group of the (meth)acrylate polymer (a1) is a glycidyl group, the functional group of the unsaturated group-containing compound (a2) is preferably an amino group, a carboxyl group or an aziridine group.

[0070] In addition, in the above-mentioned unsaturated group-containing compound (a2), one molecule contains at least one active energy ray-polymerizable carbon-carbon double bond, preferably contains 1 to 6 active energy ray-polymerizable carbon-carbon double bonds, and further preferably contains 1 to 4 active energy ray-polymerizable carbon-carbon double bonds. Specific examples of such unsaturated group-containing compounds (a2) include 2-methacryloyloxyethyl isocyanate, 2-acryloyloxyethyl isocyanate, 2-(2-methacryloyloxyethoxy)ethyl isocyanate, 1,1-(bisacryloyloxymethyl)ethyl isocyanate, m-isopropenyl-α,α-dimethylbenzyl isocyanate, methacryloyl isocyanate, allyl isocyanate, 1,1-(bisacryloyloxymethyl)ethyl isocyanate; acryloyl monoisocyanate compounds obtained by the reaction of a diisocyanate compound or a polyisocyanate compound with hydroxyethyl (meth)acrylate; acryloyl monoisocyanate compounds obtained by the reaction of a diisocyanate compound or a polyisocyanate compound with a polyol compound and hydroxyethyl (meth)acrylate; glycidyl (meth)acrylate; (meth)acrylic acid, 2-(1-aziridinyl)ethyl (meth)acrylate, 2-vinyl-2-oxazoline, 2-isopropenyl-2-oxazoline, and the like.

[0071] The unsaturated group-containing compound (a2) is preferably used at a ratio of 50 mol% or more, particularly preferably at a ratio of 60 mol% or more, and further preferably at a ratio of 70 mol% or more, relative to the molar number of the functional group-containing monomer of the (meth) acrylic acid ester polymer (a1). In addition, the unsaturated group-containing compound (a2) is preferably used at a ratio of 95 mol% or less, particularly preferably at a ratio of 93 mol% or less, and further preferably at a ratio of 90 mol% or less, relative to the molar number of the functional group-containing monomer of the (meth) acrylic acid ester polymer (a1).

[0072] In the reaction between the (meth)acrylate polymer (a1) and the unsaturated group-containing compound (a2), the reaction temperature, pressure, solvent, time, presence or absence of a catalyst, and the type of catalyst can be appropriately selected according to the combination of the functional groups of the (meth)acrylate polymer (a1) and the functional groups of the unsaturated group-containing compound (a2). Thus, the functional groups present in the (meth)acrylate polymer (a1) react with the functional groups in the unsaturated group-containing compound (a2), and the unsaturated groups are introduced into the side chains of the (meth)acrylate polymer (a1), thereby obtaining an active energy ray-curable polymer (A).

[0073] The weight average molecular weight (Mw) of the active energy ray curable polymer (A) obtained in this way is preferably 10,000 or more, particularly preferably 150,000 or more, and further preferably 200,000 or more. In addition, the weight average molecular weight (Mw) is preferably 1.5 million or less, particularly preferably 1 million or less. In addition, the weight average molecular weight (Mw) in this specification is a value calculated using standard polystyrene measured by gel permeation chromatography (GPC method).

[0074] (2) Alkylene glycol modified rosin ester

[0075] The alkylene glycol-modified rosin ester is not particularly limited, but preferably is an alkylene glycol-modified rosin ester obtained by esterification reaction of rosins, polyalkylene glycol monoalkyl ethers, polyhydric alcohols, and α,β-unsaturated carboxylic acids.

[0076] In addition, as the above-mentioned alkylene glycol-modified rosin ester, it is preferred to use an alkylene glycol-modified rosin ester having a softening point of 50°C or less, particularly preferably an alkylene glycol-modified rosin ester having a softening point of 20°C or less, and further preferably an alkylene glycol-modified rosin ester having a softening point of 0°C or less. By setting the softening point to 50°C or less, the fluidity of the alkylene glycol-modified rosin ester becomes higher, and as a result, it is easy to suppress excessive increase in the adhesion of the workpiece processing sheet of the present embodiment to the active surface of the workpiece. In addition, the lower limit of the above-mentioned softening point is not particularly limited, but is preferably -100°C or more, particularly preferably -70°C or more, and further preferably -40°C or more.

[0077] In addition, as the above-mentioned alkylene glycol modified rosin ester, it is preferred to use an alkylene glycol modified rosin ester with a weight average molecular weight of more than 1000, and it is particularly preferred to use an alkylene glycol modified rosin ester with a weight average molecular weight of more than 2000, and it is further preferred to use an alkylene glycol modified rosin ester with a weight average molecular weight of more than 3000. By making the weight average molecular weight more than 1000, the compatibility of the alkylene glycol modified rosin ester and other components in the adhesive composition is easy to moderately reduce, and as a result, it is easy to suppress the excessive rise of the adhesion of the workpiece processing sheet of the present embodiment to the active surface of the workpiece. In addition, from the perspective of compatibility with the adhesive composition, the upper limit of the above-mentioned weight average molecular weight is preferably less than 1,000,000, more preferably less than 100,000, particularly preferably less than 50,000, and more preferably less than 8000.

[0078] Relative to 100 parts by mass of acrylic polymers (active energy ray curing polymers (A)) having active energy ray curing groups introduced in the side chain, the content of the alkylene glycol modified rosin ester in the adhesive composition is preferably 0.01 parts by mass or more, particularly preferably 0.1 parts by mass or more, and further preferably 0.5 parts by mass or more. By making the above content 0.01 parts by mass or more, it is easy to effectively suppress the excessive rise of the adhesion as described above. In addition, relative to 100 parts by mass of acrylic polymers (active energy ray curing polymers (A)) having active energy ray curing groups introduced in the side chain, the above content is preferably 25 parts by mass or less, particularly preferably 8 parts by mass or less, and further preferably 4 parts by mass or less. By making the above content 25 parts by mass or less, the workpiece processing sheet of the present embodiment is easy to have the required adhesion to the workpiece when processing the workpiece.

[0079] (3) Hindered amine stabilizer

[0080] In this specification, a hindered amine stabilizer refers to a stabilizer having one or more amine skeletons in a molecule. The hindered amine stabilizer in this embodiment is not particularly limited as long as it has such a structure.

[0081] In addition, as hindered amine stabilizers, there are generally the following stabilizers, etc.: N-alkyl hindered amine stabilizers, which are compounds having a structure in which one or two or more alkyl groups are bonded to the nitrogen atom of the 2,2,6,6-tetramethylpiperidine skeleton in the molecule; N-alkoxy hindered amine stabilizers, which are compounds having a structure in which one or two or more alkoxy groups are bonded to the nitrogen atom of the 2,2,6,6-tetramethylpiperidine skeleton in the molecule; NH-type hindered amine stabilizers, which are compounds having a structure in which one or two or more hydrogen atoms are bonded to the nitrogen atom of the 2,2,6,6-tetramethylpiperidine skeleton in the molecule. In the workpiece processing sheet of the present embodiment, any of the above compounds can be used to obtain good effects, but from the perspective of being easy to separate the workpiece even after long-term storage in a state of being attached to the active surface of the workpiece, it is preferred to use an N-alkyl hindered amine stabilizer.

[0082] Examples of the alkyl group in the above-mentioned N-alkyl hindered amine stabilizer include methyl, ethyl, n-propyl, isopropyl, n-butyl, n-pentyl, n-hexyl, n-octyl and the like. Among them, methyl is preferred from the viewpoint of being easy to separate from the workpiece even after long-term storage in a state of being attached to the active surface of the workpiece.

[0083] Specific examples of hindered amine stabilizers include p,p'-dioctyldiphenylamine, phenyl-α-naphthylamine, poly(2,2,4-trimethyl-1,2-dihydroquinoline), 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, N,N'-diphenyl-p-phenylenediamine, N,N'-di-β-naphthyl-p-phenylenediamine, N-phenyl-N'-isopropyl-p-phenylenediamine, N,N'-diallyl-p-phenylenediamine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, 4-methyl-N-[4-(anilino)phenyl]benzenesulfonamide, N-phenyl-N'-(3-methacryloyloxy-2-hydroxypropyl)-p-phenylenediamine, N-(1-methylheptyl)-N'-phenyl-p-phenylenediamine, Phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, N-phenyl-N'-1,3-dimethylbutyl-p-phenylenediamine, alkylated diphenylamine, polycondensation product of dimethyl succinate and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine, poly[[6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl-[(2,2,6,6-tetramethyl-4-piperidinyl)imino]], N,N'-bis(3-aminopropyl)ethylenediamine and 2,4-bis[N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidinyl )amino]-6-chloro-1,3,5-triazine condensate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, 2-(3,5-di-tert-butyl-4-hydroxybenzyl)-2-n-butylmalonic acid bis(1,2,2,6,6-pentamethyl-4-piperidyl) ester, bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, 1,2,3,4-butanetetracarboxylic acid tetra(1,2,2,6,6-pentamethyl-4-piperidyl) ester, 1,2,3,4-butanetetracarboxylic acid tetra(2,2,6,6-tetramethyl-4-piperidyl) ester, 1,2,3,4- A mixed ester of butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and 1-tridecanol, a mixed ester of 1,2,3,4-butanetetracarboxylic acid with 2,2,6,6-tetramethyl-4-piperidinol and 1-tridecanol, a mixed ester of 1,2,3,4-butanetetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane, a mixed ester of 1,2,3,4-butanetetracarboxylic acid with 2,2,6,6-tetramethyl-4-piperidinol and 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane.5] Undecane mixed esters, (2,2,6,6-tetramethylene-4-piperidinyl)-2-propenecarboxylate, (1,2,2,6,6-pentamethyl-4-piperidinyl)-2-propenecarboxylate, etc.

[0084] Among the above specific examples, a mixed ester of 1,2,3,4-butanetetracarboxylic acid, 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane is preferably used as an N-alkyl hindered amine stabilizer.

[0085] In addition, as the hindered amine stabilizer, it is preferred to use a hindered amine stabilizer with a molecular weight of 500 or more, particularly preferably a hindered amine stabilizer with a molecular weight of 1000 or more, and further preferably a hindered amine stabilizer with a molecular weight of 2000 or more. By making the molecular weight of 500 or more, the compatibility of the hindered amine stabilizer with other components in the adhesive composition is easily reduced appropriately, and as a result, it is easy to suppress the excessive increase in the adhesion of the workpiece processing sheet of this embodiment to the active surface of the workpiece. In addition, from the perspective of compatibility with the adhesive composition, the upper limit of the molecular weight is preferably 1,000,000 or less, more preferably 100,000 or less, particularly preferably 50,000 or less, and further preferably 8,000 or less.

[0086] In addition, the molar mass of the hindered amine stabilizer is preferably 200 g / mol or more, particularly preferably 600 g / mol or more, and further preferably 1000 g / mol or more. In addition, the molar mass is preferably 10000 g / mol or less, particularly preferably 5000 g / mol or less, and further preferably 3000 g / mol or less. By setting the molar mass of the hindered amine stabilizer to the above range, even after long-term storage in a state of being attached to the active surface of the workpiece, it is still easy to achieve simple separation of the workpiece.

[0087] The content of the hindered amine stabilizer in the adhesive composition is preferably 0.1 parts by mass or more, particularly preferably 0.5 parts by mass or more, and further preferably 1.0 parts by mass or more relative to 100 parts by mass of an acrylic polymer having an active energy ray-curable group introduced into the side chain (active energy ray-curable polymer (A)). In addition, the content is preferably 30 parts by mass or less, particularly preferably 20 parts by mass or less, and further preferably 15 parts by mass or less. By making the content of the hindered amine stabilizer within the above range, even after long-term storage in a state of being attached to the active surface of the workpiece, it is still easy to achieve simple separation of the workpiece.

[0088] (4) Cross-linking agent

[0089] The above-mentioned adhesive composition also preferably contains a crosslinking agent. By making the adhesive composition contain a crosslinking agent, in the adhesive layer, the active energy ray-curable polymer (A) is crosslinked to form a good three-dimensional network structure. Thus, the cohesive force of the obtained adhesive is further increased, and the generation of residual glue on the workpiece separated from the workpiece processing sheet after irradiation with active energy rays can be effectively suppressed. In addition, when the adhesive composition contains a crosslinking agent, the active energy ray-curable polymer (A) preferably contains the above-mentioned functional group-containing monomer as a monomer unit constituting the polymer, and particularly preferably contains a functional group-containing monomer having a high reactivity with the crosslinking agent used as a monomer unit constituting the polymer.

[0090] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, ammonium salt crosslinking agents, etc. These crosslinking agents can be selected based on the functional group from the functional group-containing monomer possessed by the acrylic copolymer. In addition, these crosslinking agents can be used alone or in combination of two or more.

[0091] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate; and their biuret bodies and isocyanurate bodies; and adducts as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among them, the isocyanurate body of hexamethylene diisocyanate is preferably used, and at least one of the isocyanurate trimer of 1,6-hexamethylene diisocyanate, trimethylolpropane-modified toluene diisocyanate, and trimethylolpropane-modified hexamethylene diisocyanate is particularly preferably used.

[0092] When the above-mentioned adhesive composition contains a crosslinking agent, relative to 100 parts by mass of active energy ray-curable polymer (A), the content of the crosslinking agent in the adhesive composition is preferably 0.01 parts by mass or more, particularly preferably 0.1 parts by mass or more, and further preferably 0.4 parts by mass or more. In addition, the content is preferably 20 parts by mass or less, particularly preferably 5 parts by mass or less. By making the content of the crosslinking agent more than 0.01 parts by mass, it is easy to improve the cohesive force of the adhesive layer after irradiation with active energy rays, thereby, it is possible to effectively suppress residual glue. In addition, by making the content of the crosslinking agent less than 20 parts by mass, the degree of crosslinking becomes appropriate, and the adhesive layer easily exerts the required adhesion.

[0093] (5) Photopolymerization initiator

[0094] The adhesive composition in this embodiment also preferably contains a photopolymerization initiator. When the adhesive composition contains a photopolymerization initiator, the polymerization curing time and the light irradiation amount when the adhesive layer is cured by irradiating active energy rays can be reduced.

[0095] Examples of the photopolymerization initiator include benzophenone, acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin benzoic acid, benzoin benzoic acid methyl ester, benzoin dimethyl ketal, 2,4-diethylthioxanthone, 1-hydroxycyclohexyl phenyl ketone, benzyl phenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, benzil, dibenzil, diacetyl, β-chloroanthraquinone, ( 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one), (2,4,6-trimethylbenzyldiphenyl)phosphine oxide, N,N-diethyldithiocarbamate 2-benzothiazolyl ester, oligomeric {2-hydroxy-2-methyl-1-[4-(1-propenyl)phenyl]propanone}, 2,2-dimethoxy-1,2-diphenylethane-1-one, etc. Among them, at least one of 1-hydroxycyclohexyl phenyl ketone and (2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propane-1-one) is preferably used. The above-mentioned photopolymerization initiators can be used alone or in combination of two or more.

[0096] When the above-mentioned adhesive composition contains a photopolymerization initiator, relative to 100 parts by mass of active energy ray-curable polymer (A), the content of the photopolymerization initiator in the adhesive composition is preferably 0.1 parts by mass or more, particularly preferably 1 parts by mass or more. In addition, the content is preferably 20 parts by mass or less, particularly preferably 5 parts by mass or less. By making the content of the photopolymerization initiator the above-mentioned range, the adhesive layer can be cured efficiently by irradiating active energy rays, thereby, it is easy to make the workpiece processing sheet to the adhesion of the adherend well reduced.

[0097] (6) Other ingredients

[0098] The adhesive composition may contain any desired additives such as silane coupling agents, antistatic agents, tackifiers, antioxidants, softeners, fillers, refractive index adjusters, etc., as long as the above effects of the workpiece processing sheet of this embodiment are not impaired.

[0099] Among the above-mentioned additives, antistatic agents are particularly preferably used. The workpiece processing sheet may usually be charged during transportation or use, and this charging may cause damage to semiconductor chips or malfunctions of cutting devices. For example, when separating the processed workpiece from the workpiece processing sheet, static electricity called peeling charging may be generated between the workpiece processing sheet and the processed workpiece. When the processed workpiece is, for example, a semiconductor chip, this static electricity may cause the circuit formed on the chip to be destroyed. The workpiece processing sheet of the present embodiment is easy to suppress the above-mentioned charging by using an antistatic agent, and is easy to perform good workpiece processing.

[0100] The antistatic agent is not particularly limited, and examples thereof include conductive polymers, conductive fillers, anionic or cationic compounds, and compounds having a quaternary ammonium base in the main chain or side chain of the molecule.

[0101] Examples of anionic or cationic compounds include ionic liquids, ionic solids, anionic surfactants, alkali metal salts, cationic surfactants, nonionic surfactants, etc. Examples of ionic liquids and ionic solids include nitrogen-containing onium salts, sulfur-containing onium salts, phosphorus-containing onium salts, boron-containing onium salts, etc. In addition, as alkali metal salts, lithium salts, potassium salts, etc. can be listed. These substances can be used alone or in combination of two or more.

[0102] When the adhesive composition contains an antistatic agent, the content of the antistatic agent in the adhesive composition is preferably 1 part by mass or more, particularly preferably 3 parts by mass or more, relative to 100 parts by mass of the active energy ray-curable polymer (A). In addition, the content is preferably 20 parts by mass or less, particularly preferably 15 parts by mass or less. By making the content of the antistatic agent the above range, it is easy to effectively suppress the above-mentioned charging.

[0103] (7) Method for preparing adhesive composition

[0104] The adhesive composition in this embodiment can be prepared by preparing an active energy ray-curable polymer (A), mixing the obtained active energy ray-curable polymer (A), an alkylene glycol-modified rosin ester, a hindered amine stabilizer, a cross-linking agent as required, a photopolymerization initiator and required additives. At this time, a diluting solvent can also be added as required to obtain a coating liquid of the adhesive composition.

[0105] As the above-mentioned diluting solvent, for example, aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as dichloromethane and ethylene chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; cellosolve-based solvents such as ethyl cellosolve, etc. can be used.

[0106] As the concentration and viscosity of the coating solution prepared in this way, as long as it is within the scope of coating, there is no particular limitation and it can be appropriately selected according to the situation. For example, the concentration of the adhesive composition is diluted in a manner of 10% by mass or more and 60% by mass or less. In addition, it is not necessary to add a diluting solvent when obtaining the coating solution. If the adhesive composition is a viscosity that can be coated, it is also possible not to add a diluting solvent. At this time, the adhesive composition is a coating solution in which the polymerization solvent of the acrylic copolymer (a1) is directly used as a diluting solvent.

[0107] (8) Thickness of adhesive layer

[0108] The thickness of the adhesive layer in this embodiment is preferably 1 μm or more, particularly preferably 3 μm or more, and more preferably 4 μm or more. By making the thickness of the adhesive layer 1 μm or more, the workpiece processing sheet is easy to exert good adhesion and easy to suppress chip scattering. In addition, the thickness is preferably 75 μm or less, particularly preferably 30 μm or less, and more preferably 20 μm or less. By making the thickness of the adhesive layer 75 μm or less, it is easy to separate the workpiece.

[0109] 3. Other components

[0110] In the workpiece processing sheet of the present embodiment, before the surface of the adhesive layer opposite to the substrate (adhesive surface) is attached to the workpiece, a release sheet may be laminated on the surface for the purpose of protecting the surface.

[0111] The release sheet may be of any structure, and may be a release sheet obtained by subjecting a plastic film to a release treatment using a release agent or the like. Specific examples of the plastic film include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; and polyolefin films such as polypropylene and polyethylene. As the release agent, silicone-based, fluorine-based, long-chain alkyl, and rubber-based ones may be used, and silicone-based ones are preferred because they are inexpensive and can provide stable performance.

[0112] The thickness of the release sheet is not particularly limited, and may be, for example, 16 μm or more and 250 μm or less.

[0113] In addition, in the workpiece processing sheet of the present embodiment, an adhesive layer can be stacked on the surface of the adhesive layer opposite to the substrate. At this time, the workpiece processing sheet of the present embodiment can be used as a cutting and solidifying chip. By attaching a workpiece to the surface of the adhesive layer in the sheet opposite to the adhesive layer, and cutting the workpiece together with the adhesive layer, a chip stacked with a singulated adhesive layer can be obtained. The chip can be simply fixed to an object to be loaded with the chip through the singulated adhesive layer. As the material constituting the above-mentioned adhesive layer, it is preferred to use a material containing a thermoplastic resin and a low molecular weight thermosetting adhesive component or a material containing a B-stage (semi-cured) thermosetting adhesive component.

[0114] Furthermore, in the workpiece processing sheet of the present embodiment, a protective film forming layer can be stacked on the adhesive surface of the adhesive layer. In this case, the workpiece processing sheet of the present embodiment can be used as a protective film forming and cutting sheet. By attaching a workpiece to the surface of the protective film forming layer in such a sheet that is opposite to the adhesive layer, and cutting the workpiece together with the protective film forming layer, a chip stacked with a singulated protective film forming layer can be obtained. As the workpiece, it is preferred to use a workpiece having a circuit formed on one side, in which case a protective film forming layer is usually stacked on the surface opposite to the surface having the circuit formed. By curing the singulated protective film forming layer at a specified time, a protective film with sufficient durability can be formed on the chip. Preferably, the protective film forming layer is formed of an uncured curable adhesive.

[0115] 4. Physical properties of workpiece processing sheets

[0116] (1) Adhesion before irradiation with active energy rays

[0117] In the workpiece processing sheet of the present embodiment, before the workpiece processing sheet is irradiated with active energy rays, the adhesion of the workpiece processing sheet to the mirror surface of the silicon wafer is preferably 1000mN / 25mm or more, particularly preferably 2000mN / 25mm or more, and further preferably 3000mN / 25mm or more. As described above, the workpiece processing sheet of the present embodiment is formed by making the adhesive layer composed of an adhesive formed by using an adhesive composition containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer, and can achieve the above-mentioned adhesion before irradiating active energy rays. By making the above-mentioned adhesion more than 1000mN / 25mm, it is easy to fix the workpiece well on the adhesive surface of the workpiece processing sheet. As a result, the workpiece can be processed more well, for example, when cutting, it can effectively suppress chipping or chip flying. In addition, the above-mentioned adhesion is preferably less than 20000mN / 25mm, particularly preferably less than 17000mN / 25mm, and more preferably less than 15000mN / 25mm. By making the above-mentioned adhesion less than 20000mN / 25mm, it is easy to further suppress the excessive increase of the adhesion to the active surface of the workpiece. In addition, the mirror surface of the above-mentioned silicon wafer is not an active surface. In addition, the details of the method for measuring the above-mentioned adhesion are described in the test examples described later.

[0118] (2) Adhesion to the active surface before irradiation with active energy rays

[0119] In the workpiece processing sheet of the present embodiment, the adhesive surface in the workpiece processing sheet is attached to the grinding surface 5 minutes after the surface of the self-grinding silicon wafer. After 20 minutes, the adhesion of the workpiece processing sheet to the above-mentioned grinding surface before the active energy ray irradiation is preferably 3000mN / 25mm or more, particularly preferably 5000mN / 25mm or more, and further preferably 7000mN / 25mm or more. As described above, the workpiece processing sheet of the present embodiment is formed by making the adhesive layer by using an adhesive composition containing alkylene glycol modified rosin ester and hindered amine stabilizer. It is possible to achieve the above-mentioned adhesion before irradiating active energy rays. By making the above-mentioned adhesion more than 3000mN / 25mm, it is easy to fix the workpiece well on the adhesive surface of the workpiece processing sheet. As a result, the workpiece can be processed more well, for example, when cutting, it is possible to effectively suppress the collapse of the edge or the scattering of the chip. In addition, the above-mentioned adhesive force is preferably less than 20000mN / 25mm, particularly preferably less than 17000mN / 25mm, and more preferably less than 15000mN / 25mm. By making the above-mentioned adhesive force less than 20000mN / 25mm, it is easy to further suppress the excessive increase of the closeness to the active surface of the workpiece. In addition, the details of the method for measuring the above-mentioned adhesive force are described in the test examples described later.

[0120] (3) Adhesion to the active surface after irradiation with active energy rays

[0121] In the workpiece processing sheet of the present embodiment, the adhesive surface in the workpiece processing sheet is attached to the grinding surface within 5 minutes from the surface of the self-grinding silicon wafer. After 7 days, after further irradiating the workpiece processing sheet with active energy rays, the adhesion of the workpiece processing sheet to the above-mentioned grinding surface is preferably 400mN / 25mm or less, more preferably 300mN / 25mm or less, particularly preferably 200mN / 25mm or less, and further preferably 150mN / 25mm or less. By making the above-mentioned adhesion less than 150mN / 25mm, even when using a workpiece with an active surface as a workpiece, it is easy to separate the processed workpiece well from the workpiece processing sheet. As described above, the workpiece processing sheet of the present embodiment is formed by making the adhesive layer composed of an adhesive composition containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer, so that the above-mentioned adhesion can be achieved even on the active surface of the workpiece. In addition, the above-mentioned adhesive force is preferably 10mN / 25mm or more, particularly preferably 50mN / 25mm or more, and further preferably 70mN / 25mm or more. By making the above-mentioned adhesive force 10mN / 25mm or less, it is easy to effectively suppress the accidental detachment of the processed workpiece from the workpiece processing sheet after irradiation with active energy rays. In addition, the details of the method for measuring the above-mentioned adhesive force are described in the test examples described later.

[0122] (4) Surface resistivity before active energy ray irradiation

[0123] In the workpiece processing sheet of the present embodiment, the surface resistivity of the adhesive layer before irradiation with active energy rays is preferably 1×10 13 Ω / cm 2 Below, particularly preferably 1×10 12 Ω / cm 2 Below, more preferably 2×10 11 Ω / cm 2 The lower limit of the surface resistivity of the adhesive layer before ultraviolet irradiation is not particularly limited, and may be, for example, 1×10 7 Ω / cm 2 By making the workpiece processing sheet of this embodiment have the above surface resistivity, when the workpiece processing sheet is peeled off from the workpiece, it is easy to effectively prevent the workpiece from being damaged due to peeling electrification. In addition, the details of the method for measuring the surface resistivity are described in the test examples described later.

[0124] 5. Method for manufacturing sheet for workpiece processing

[0125] The method for producing the workpiece processing sheet of the present embodiment is not particularly limited, but it is preferably produced by laminating an adhesive layer on one side of a substrate.

[0126] The adhesive layer can be stacked on the single side of the substrate using a known method. For example, the adhesive layer formed on the release sheet is preferably transferred to the single side of the substrate. At this time, an adhesive composition containing an adhesive layer and a coating liquid containing a solvent or a dispersion medium as required is prepared, and a die coater, a curtain coater, a spray coater, a slit coater, a blade coater, a roller knife coater, an applicator, etc. are used to apply the coating liquid on the peeling-processed surface of the release sheet (hereinafter, sometimes referred to as "peeling surface") to form a coating film, and the coating film is dried, thereby forming an adhesive layer. As long as it can be coated, the properties of the coating liquid are not particularly limited, and there is a situation in which the components used to form the adhesive layer are contained in the form of a solute, and there is also a situation in which the components used to form the adhesive layer are contained in the form of a dispersion (dispersoid). The release sheet in the laminate can be peeled off as a process material, and can also be used to protect the adhesive surface of the adhesive layer during the period before the workpiece processing sheet is attached to the adherend.

[0127] When the coating liquid for forming the adhesive layer contains a crosslinking agent, the active energy ray-curable polymer (A) in the coating film and the crosslinking agent are crosslinked by changing the above-mentioned drying conditions (temperature, time, etc.) or by providing a heat treatment, so as to form a crosslinked structure in the adhesive layer at a desired density. In order to fully carry out the crosslinking reaction, after laminating the adhesive layer on the substrate using the above-mentioned method, the following aging can be carried out: for example, the obtained workpiece processing sheet is left to stand for several days under an environment of 23°C and a relative humidity of 50%.

[0128] Instead of transferring the adhesive layer formed on the release sheet to one side of the substrate as described above, the adhesive layer can be directly formed on the substrate. In this case, the adhesive layer is formed by applying the coating liquid for forming the adhesive layer on one side of the substrate to form a coating film, and the coating film is dried to form the adhesive layer.

[0129] 6. How to use the workpiece processing sheet

[0130] The workpiece processing sheet of the present embodiment can be used for processing a workpiece. That is, after the adhesive surface of the workpiece processing sheet of the present embodiment is attached to a single side of the workpiece, the workpiece can be processed on the workpiece processing sheet. Examples of such processing include back grinding, cutting, expansion, picking up, etc. The above-mentioned cutting can be, for example, blade cutting using a rotating circular blade, laser cutting that fully cuts a semiconductor wafer by irradiating a laser, or stealth cutting that forms a modified layer on the semiconductor wafer by irradiating a laser, and then stretching the semiconductor wafer to divide the semiconductor wafer at the modified layer. The workpiece processing sheet of the present embodiment can be used as a back grinding sheet, a cutting sheet, an expansion sheet, a picking sheet, etc., depending on the type of processing.

[0131] As examples of workpieces processed using the workpiece processing sheet of the present embodiment, semiconductor components such as semiconductor wafers and semiconductor packages; glass components such as glass plates can be cited. Among them, as described above, even when the adhesive surface is attached to the active surface of a workpiece having an active surface, the workpiece processing sheet of the present embodiment can still well suppress the increase in the adhesion of the workpiece processing sheet to the active surface. Therefore, the workpiece processing sheet of the present embodiment is suitable for processing a workpiece having an active surface (especially the surface of a semiconductor wafer that has been ground within 120 minutes from the grinding surface). However, the workpiece processing sheet of the present embodiment can be attached to any one of a workpiece having an active surface (especially the surface of a semiconductor wafer that has been ground within 120 minutes from the grinding surface), and a normal workpiece that does not have an active surface (especially the surface other than the surface of a semiconductor wafer that has been ground within 120 minutes from the grinding surface).

[0132] When the workpiece is processed on the workpiece processing sheet of the present embodiment and the processed workpiece is separated from the workpiece processing sheet, it is preferred that the adhesive layer in the workpiece processing sheet is irradiated with active energy rays before the separation. Thus, the adhesive layer is cured, the adhesion of the workpiece processing sheet to the processed workpiece is well reduced, and the separation of the processed workpiece becomes easy.

[0133] As the above-mentioned active energy ray, for example, active energy ray having energy quantum in electromagnetic wave or charged particle beam can be used, specifically, ultraviolet ray or electron beam can be used. Ultraviolet ray which is easy to operate is particularly preferred. Ultraviolet ray irradiation can be carried out using a high pressure mercury lamp, a xenon lamp, an LED, etc., and the irradiation intensity of ultraviolet ray is preferably 1 mW / cm 2 Above and 1000mW / cm 2 In addition, the light intensity is preferably 10 mJ / cm 2 Above, particularly preferably 80 mJ / cm 2 More preferably, 150 mJ / cm 2In addition, the light intensity is preferably 10000 mJ / cm 2 Below, particularly preferably 5000 mJ / cm 2 Below, more preferably 2000mJ / cm 2 On the other hand, the electron beam irradiation can be performed by an electron beam accelerator or the like, and the irradiation amount of the electron beam is preferably 10 krad or more and 1000 krad or less.

[0134] The workpiece processing sheet of this embodiment is particularly preferably used in a method for manufacturing a processed workpiece having the following steps. That is, the method for manufacturing a processed workpiece has the following steps: a grinding step of grinding the surface of the workpiece; a step of attaching the workpiece processing sheet of this embodiment to the ground surface of the workpiece; a step of cutting the workpiece on the workpiece processing sheet to obtain chips formed by singulating the workpiece; an active energy ray irradiation step of irradiating the adhesive layer in the workpiece processing sheet with active energy rays; and a step of picking up the chips one by one from the workpiece processing sheet.

[0135] The above-mentioned grinding process can be carried out using a conventionally known method. For example, the adhesive surface of the desired adhesive sheet (which can be a workpiece processing sheet of the present embodiment) is attached to one face of the workpiece, and a grinding device is used to grind the other face of the workpiece on the above-mentioned adhesive sheet. The degree of grinding at this time can be selected according to the purpose, for example, grinding to the thickness of the workpiece or the state of the surface reaches a prescribed degree. After the grinding, the surface that has been ground can be subjected to conventionally known surface treatment.

[0136] In the subsequent attaching process, as long as the adhesive surface of the workpiece processing sheet of the present embodiment is attached to the grinding surface of the workpiece, the specific method is not limited. Here, the time from the surface grinding of the workpiece in the above-mentioned grinding process to the above-mentioned attachment can be within 120 minutes, especially within 30 minutes, and further within 5 minutes. When the above-mentioned time is within 120 minutes, although the grinding surface of the workpiece is an active surface that maintains an activated state, according to the workpiece processing sheet of the present embodiment, even for such an active surface, the excessive rise of adhesion can be suppressed, and it can also be picked up well in the picking-up process described later.

[0137] The subsequent cutting process can be performed using a conventionally known method. That is, a cutting device is used to cut the workpiece on the workpiece processing sheet to obtain a plurality of chips formed by singulating the workpiece. The type of cutting here is not particularly limited, and can be, for example, blade cutting, laser cutting, stealth cutting, etc.

[0138] The irradiation with active energy rays in the active energy ray irradiation step can be performed by a conventionally known method. The type of active energy rays and the irradiation conditions are as described above.

[0139] Picking up in the subsequent picking up process can also be performed using a conventionally known method. For example, picking up can be performed in the following manner: using a picking up device, expanding the workpiece processing sheet, and using a needle to lift up the semiconductor chip from the back of the workpiece processing sheet, and further using a suction head to take out the chip. According to the workpiece processing sheet of this embodiment, the excessive increase in the adhesion between the workpiece and the chip can be suppressed, thereby avoiding the problem of being unable to pick up the chip, and enabling good picking up.

[0140] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes and equivalents within the technical scope of the present invention.

[0141] For example, another layer may be provided between the substrate and the adhesive layer, or another layer may be provided on the surface of the substrate opposite to the adhesive layer.

[0142] Example

[0143] Hereinafter, the present invention will be described in more detail using examples and the like, but the scope of the present invention is not limited to these examples and the like.

[0144] [Example 1]

[0145] (1) Preparation of substrate

[0146] Ethylene-methacrylic acid copolymer (EMAA) (manufactured by Dupont-Mitsui Polychemicals Co., Ltd., product name "NUCREL N0903HC") was extruded using a small T-die extruder (manufactured by Toyo Seiki Seisaku-sho, Ltd., product name "LaboPlastomill") to obtain an EMAA film with a thickness of 80 μm. In addition, both sides of the obtained EMAA film were corona treated. Thus, a substrate was obtained.

[0147] (2) Preparation of adhesive composition

[0148] 52 parts by mass of n-butyl acrylate, 20 parts by mass of methyl methacrylate, and 28 parts by mass of 2-hydroxyethyl acrylate were polymerized by a solution polymerization method to obtain a (meth)acrylate polymer.

[0149] The obtained (meth)acrylate polymer was reacted with methacryloyloxyethyl isocyanate (MOI) to obtain an acrylic polymer (active energy ray curable polymer) having an active energy ray curable group introduced into the side chain, wherein the methacryloyloxyethyl isocyanate (MOI) was present in an amount corresponding to 90 mol% relative to 2-hydroxyethyl acrylate constituting the (meth)acrylate polymer. The weight average molecular weight (Mw) of the active energy ray curable polymer was measured by the method described below and was 660,000.

[0150] 35 parts by mass of the obtained active energy ray-curable polymer, 0.375 parts by mass of a trimethylolpropane adduct of 1,6-hexamethylene diisocyanate (manufactured by TOSOH CORPORATION, product name "CORONATE HL") as a crosslinking agent, 0.47 parts by mass of 1-hydroxycyclohexyl phenyl ketone (manufactured by BASF, product name "Irgacure 184") as a photopolymerization initiator, and 1 part by mass of an alkylene glycol-modified rosin ester (manufactured by Arakawa Chemical Co., Ltd.) were mixed in a solvent. Industries, Ltd., product name "D-6250"), 1 part by mass of a mixed ester of 1,2,3,4-butanetetracarboxylic acid, 1,2,2,6,6-pentamethyl-4-piperidinol and 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane as a hindered amine stabilizer (N-methyl hindered amine stabilizer, ADEKA CORPORATION, product name "ADK STAB LA-63P"), and a coating liquid of the adhesive composition (solid content concentration of 30% by mass) was obtained.

[0151] (3) Formation of Adhesive Layer

[0152] The coating liquid of the adhesive composition obtained in the above step (2) was applied to the release surface of a release sheet (manufactured by LINTEC Corporation, product name "SP-PET381031") having a silicone release layer formed on one side of a polyethylene terephthalate film having a thickness of 38 μm, and the film was dried by heating to obtain a laminate having an adhesive layer having a thickness of 5 μm formed on the release sheet.

[0153] (4) Preparation of adhesive sheet

[0154] One surface of the substrate obtained in the step (1) was bonded to the adhesive layer side surface of the laminate obtained in the step (3), and then stored in a light-shielded state at 23° C. and 50% environment for 10 days. Thus, a workpiece processing sheet was obtained.

[0155] (5) Determination of weight average molecular weight (Mw) of (meth)acrylate copolymer

[0156] The weight average molecular weight (Mw) of the (meth)acrylate copolymer is a polystyrene-equivalent weight average molecular weight measured under the following conditions using gel permeation chromatography (GPC) (GPC measurement).

[0157] <Measurement conditions>

[0158] ·GPC measuring apparatus: manufactured by TOSOH CORPORATION, HLC-8320

[0159] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION

[0160] TSK gel superH-H

[0161] TSK gel superHM-H

[0162] TSK gel superH2000

[0163] ·Test solvent: tetrahydrofuran

[0164] ·Measurement temperature: 40℃

[0165] [Examples 2 to 4 and Comparative Examples 1 to 5]

[0166] Except having changed the content of the alkylene glycol-modified rosin ester, the hindered amine stabilizer, and the crosslinking agent as shown in Table 1, it carried out similarly to Example 1, and obtained the sheet for workpiece processing.

[0167] [Example 5]

[0168] A workpiece processing sheet was obtained in the same manner as in Example 1 except that 1.87 parts by mass of an ionic solid (manufactured by Japan Carlit Co., Ltd., product name “CIL-H11”) was added as an antistatic agent when preparing the adhesive composition.

[0169] [Examples 6 to 8]

[0170] Except having changed the content of the alkylene glycol-modified rosin ester, the hindered amine stabilizer, and the crosslinking agent as shown in Table 1, it carried out similarly to Example 5 to obtain a workpiece processing sheet.

[0171] [Test Example 1] (Measurement of Adhesion Force Before Active Energy Ray Irradiation)

[0172] The workpiece processing sheets manufactured in the examples and comparative examples were cut into strips with a width of 25 mm. Under an environment of a temperature of 23° C. and a relative humidity of 50%, a 2 kg rubber roller was used to peel off the peeling sheet from the obtained strip-shaped workpiece processing sheet, and the adhesive surface of the adhesive layer exposed was attached to the mirror surface of the mirror-finished silicon wafer, which was used as a measurement sample.

[0173] For the obtained measurement sample, 20 minutes after being attached to the silicon wafer, a universal tensile tester (manufactured by ORIENTEC CO., LTD., product name "TENSILON UTM-4-100") was used to peel the workpiece processing sheet from the silicon wafer at a peeling speed of 300 mm / min and a peeling angle of 180° under the condition of 23°C, and the adhesion to the silicon wafer was measured using the 180° peeling method based on JIS Z0237:2009 (mN / 25mm). The measured value of the adhesion thus obtained is shown in Table 1 as the pre-UV adhesion.

[0174] Furthermore, the above measured values ​​were compared with the following criteria to evaluate the adhesiveness to the inactive surface before irradiation with active energy rays. The results are also shown in Table 1.

[0175] A: The pre-UV adhesion is 3000mN / 25mm or more.

[0176] B: The pre-UV adhesive force is 1000 mN / 25 mm or more and less than 3000 mN / 25 mm.

[0177] C: Adhesion before UV is less than 1000mN / 25mm.

[0178] [Test Example 2] (Measurement of Adhesion Force to Active Surface Before Irradiation with Active Energy Rays)

[0179] The workpiece processing sheet manufactured in the embodiment and the comparative example is cut into strips with a width of 25 mm. On the other hand, a single side of the silicon wafer is ground using a grinding device (manufactured by DISCO CORPORATION, product name "DFG8540") until the thickness of the silicon wafer becomes 600 μm and a #2000 grinding surface is obtained. Under an environment of a temperature of 23°C and a relative humidity of 50%, a 2kg rubber roller is used to attach the exposed surface of the adhesive layer exposed by peeling off the peeling sheet from the above-mentioned strip-shaped workpiece processing sheet to the grinding surface (active surface) activated by the grinding, and then let it stand for 20 minutes, and use it as a sample for measurement. In addition, the attachment of the workpiece processing sheet to the above-mentioned active surface is carried out within 5 minutes from the above-mentioned grinding.

[0180] The measurement sample was stored in an environment with a temperature of 23° C. and a relative humidity of 50%. The storage period at this time was set to 20 minutes.

[0181] After storage, a universal tensile tester (manufactured by ORIENTEC CO., LTD., product name "TENSILONUTM-4-100") was used to peel the workpiece processing sheet from the silicon wafer at a peeling speed of 300 mm / min and a peeling angle of 180°, and the adhesive force (mN / 25 mm) was measured using the 180° peeling method based on JIS Z0237:2009. The measured values ​​of the adhesive force thus obtained are shown in Table 1 as the pre-UV adhesive force on the active wafer.

[0182] Furthermore, the above-mentioned measured values ​​were compared with the following criteria to evaluate the adhesion to the active wafer before irradiation with active energy rays.

[0183] A: The pre-UV adhesion to active wafers is above 4000mN / 25mm.

[0184] B: The pre-UV adhesion to the active wafer is 3000mN / 25mm or more and less than 4000mN / 25mm.

[0185] C: The pre-UV adhesion to active wafer is less than 3000mN / 25mm.

[0186] [Test Example 3] (Measurement of Adhesion to Active Surface after Active Energy Ray Irradiation)

[0187] The workpiece processing sheet manufactured in the embodiment and the comparative example is cut into strips with a width of 25 mm. On the other hand, a single side of the silicon wafer is ground using a grinding device (manufactured by DISCO CORPORATION, product name "DFG8540") until the thickness of the silicon wafer becomes 600 μm and a #2000 grinding surface is obtained. Under an environment of a temperature of 23°C and a relative humidity of 50%, a 2kg rubber roller is used to attach the exposed surface of the adhesive layer exposed by peeling off the peeling sheet from the above-mentioned strip-shaped workpiece processing sheet to the grinding surface (active surface) activated by the grinding, and then let it stand for 20 minutes, and use it as a sample for measurement. In addition, the attachment of the workpiece processing sheet to the above-mentioned active surface is carried out within 5 minutes from the above-mentioned grinding.

[0188] The measurement sample was stored in an environment with a temperature of 23° C. and a relative humidity of 50%. The storage period at this time was set to 7 days.

[0189] After storage, the adhesive layer was irradiated with ultraviolet light (UV) (illuminance: 230 mW / cm 2 , light intensity: 190mJ / cm 2 ) to cure the adhesive layer.

[0190] Then, a universal tensile tester (manufactured by ORIENTEC CO., LTD., product name "TENSILON UTM-4-100") was used to peel the workpiece processing sheet from the silicon wafer at a peeling speed of 300 mm / min and a peeling angle of 180°, and the adhesive force (mN / 25 mm) was measured using the 180° peeling method based on JIS Z0237:2009. The measured values ​​of the adhesive force thus obtained are shown in Table 1 as the adhesive force after UV on the active wafer.

[0191] Furthermore, the above-mentioned measured values ​​were compared with the following standards to evaluate the adhesion to the active wafer after the active energy ray irradiation.

[0192] A: The post-UV adhesion of active wafers is less than 200mN / 25mm.

[0193] B: The post-UV adhesion to the active wafer is greater than 200mN / 25mm and less than 300mN / 25mm.

[0194] C: The post-UV adhesion to active wafers is greater than 300mN / 25mm.

[0195] [Test Example 4] (Evaluation of cutting suitability)

[0196] A single side of the silicon wafer was ground using a grinding device (manufactured by DISCO CORPORATION, product name "DFG8540") until the thickness of the silicon wafer became 150 μm and a #2000 grinding surface was obtained. A laminator was used to attach the adhesive surface of the adhesive layer exposed by peeling off the peeling sheet from the workpiece processing sheet manufactured in the embodiment and the comparative example to the grinding surface (active surface) activated by the grinding. In addition, the attachment was performed within 5 minutes from the above grinding.

[0197] After the above-mentioned attachment, the film was stored in an environment of a temperature of 23° C. and a relative humidity of 50% for 20 minutes, and then cut under the following conditions.

[0198] <Cutting conditions>

[0199] Cutting device: DFD-6362 manufactured by DISCO CORPORATION

[0200] Blade: NBC-2H 2050 27HECC manufactured by DISCO CORPORATION

[0201] Blade width: 0.025~0.030mm

[0202] Blade exposure: 0.640~0.760mm

[0203] Blade speed: 35000rpm

[0204] Cutting speed: 60mm / sec

[0205] ·Substrate cutting depth: 20μm

[0206] Cutting water volume: 1.0L / min

[0207] Cutting water temperature: 20℃

[0208] Cutting size: 0.4mm square

[0209] After dicing, the obtained chips were visually checked, and the number of chips that had scattered was counted. The results are shown in Table 1. Furthermore, the number was compared with the following criteria to evaluate the dicing suitability.

[0210] A: The number of scattered chips is less than 10.

[0211] B: The number of chip scattering is 10 or more and less than 20.

[0212] C: The number of scattered chips is 20 or more.

[0213] [Test Example 5] (Evaluation of Pickup Suitability)

[0214] A single side of the silicon wafer was ground using a grinding device (manufactured by DISCO CORPORATION, product name "DFG8540") until the thickness of the silicon wafer became 150 μm and a #2000 grinding surface was obtained. A laminator was used to attach the adhesive surface of the adhesive layer exposed by peeling off the peeling sheet from the workpiece processing sheet manufactured in the embodiment and the comparative example to the grinding surface (active surface) activated by the grinding. In addition, the attachment was performed within 5 minutes from the above grinding.

[0215] After the above-mentioned attachment, the samples were stored in an environment of 23° C. and 50% relative humidity for 7 days and then cut under the following conditions.

[0216] <Cutting conditions>

[0217] Cutting device: DFD-6362 manufactured by DISCO CORPORATION

[0218] Blade: NBC-2H 2050 27HECC manufactured by DISCO CORPORATION

[0219] Blade width: 0.025~0.030mm

[0220] Blade exposure: 0.640~0.760mm

[0221] Blade speed: 35000rpm

[0222] Cutting speed: 60mm / sec

[0223] ·Substrate cutting depth: 20μm

[0224] Cutting water volume: 1.0L / min

[0225] Cutting water temperature: 20℃

[0226] Cutting size: 10mm square

[0227] Furthermore, the adhesive layer in the workpiece processing sheet was irradiated with ultraviolet rays (UV) (illuminance: 230 mW / cm 2 , light intensity: 190mJ / cm 2 ) to cure the adhesive layer.

[0228] Next, a pick-up device was used to try to pick up one chip located near the center when looking down at the workpiece processing sheet from among the multiple chips obtained by the above-mentioned cutting. Specifically, a pin was used to lift the chip from the surface on the substrate side of the workpiece processing sheet at a lifting height of 500 μm, and a vacuum suction head was used to adsorb the surface of the chip on the opposite side of the workpiece processing sheet, thereby trying to separate the chip from the workpiece processing sheet. The picking operation was performed on 10 chips, and the number of chips successfully separated was counted. The results are shown in Table 1.

[0229] Furthermore, the above number was compared with the following criteria to evaluate the picking suitability.

[0230] A: The number of chips successfully separated is 10.

[0231] B: The number of successfully separated chips is 1 or more and 9 or less.

[0232] C: The number of successfully separated chips is 0.

[0233] [Test Example 6] (Measurement of surface resistivity before active energy ray irradiation)

[0234] The workpiece processing sheet manufactured in the embodiment and the comparative example was cut into a size of 10 cm × 10 cm and used as a measurement sample. The surface resistivity (Ω / cm2) of the adhesive surface of the adhesive layer exposed by peeling off the release sheet from the measurement sample was measured using a surface resistivity meter (manufactured by ADVANTEST CORPORATION, product name "R8252") in accordance with JIS K7194 at a temperature of 23°C and a relative humidity of 50% with an applied voltage of 100 V. 2 ). The measurement results are shown in Table 1 as the surface resistivity before UV.

[0235] Furthermore, the above measurement results were compared with the following criteria to evaluate the antistatic properties.

[0236] A: Surface resistivity is less than 1×10 11 Ω / cm 2 .

[0237] B: Surface resistivity is 1×10 11 Ω / cm 2 above.

[0238] [Table 1]

[0239]

[0240] As shown in Table 1, the workpiece processing sheet obtained in the embodiment shows good adhesion before active energy ray irradiation, whether attached to the inactive surface of the silicon wafer or to the active surface of the silicon wafer. In addition, the workpiece processing sheet obtained in the embodiment can be fully reduced in adhesion to the workpiece by irradiation with active energy rays, even when attached to the active surface of the silicon wafer.

[0241] The workpiece processing sheets obtained in the examples were also excellent in cutting suitability and picking suitability. In addition, the workpiece processing sheets of Examples 5 to 8 in which the adhesive layer contained an antistatic agent exhibited excellent antistatic properties.

[0242] Industrial Applicability

[0243] The workpiece processing sheet of the present invention is suitable for use as a cutting sheet or the like for a workpiece having an active surface.

Claims

1. A workpiece processing sheet comprising a base material and an adhesive layer laminated on one side of the base material, wherein: The adhesive layer is composed of an active energy ray-curable adhesive containing an alkylene glycol-modified rosin ester and a hindered amine stabilizer. The workpiece processing sheet is to be attached to a surface of a workpiece that has been ground within 120 minutes from the time the surface of the workpiece is ground.

2. The workpiece processing sheet according to claim 1, characterized in that: The hindered amine stabilizer is an N-alkyl hindered amine stabilizer.

3. The workpiece processing sheet according to claim 1, characterized in that: The hindered amine stabilizer has a molecular weight of 500 or more.

4. The workpiece processing sheet according to claim 1, characterized in that: The weight average molecular weight of the alkylene glycol-modified rosin ester is 1,000 or more.

5. The workpiece processing sheet according to claim 1, characterized in that: The active energy ray-curable adhesive is formed of an adhesive composition containing an acrylic polymer having an active energy ray-curable group introduced into a side chain, the alkylene glycol-modified rosin ester, and the hindered amine stabilizer.

6. The workpiece processing sheet according to claim 5, characterized in that: The adhesive composition contains an antistatic agent.

7. A method for manufacturing a processed workpiece, characterized in that: have: A grinding process in which the surface of a workpiece is ground; A step of attaching the workpiece processing sheet according to any one of claims 1 to 6 to the polished surface of the workpiece; A dicing step of dicing the workpiece on the workpiece processing sheet to obtain a plurality of chips obtained by singulating the workpiece; an active energy ray irradiation step of irradiating the adhesive layer in the workpiece processing sheet with active energy rays; and A picking up step of picking up the chips one by one from the workpiece processing sheet.

8. The method for manufacturing a processed workpiece according to claim 7, characterized in that: The attachment of the workpiece processing sheet to the workpiece in the attachment step is performed within 120 minutes from the start of the surface grinding of the workpiece in the grinding step.